Importance of physical attractiveness in dating behavior - Walster, Elaine; Aronson, Vera (1966)
It was proposed that an individual would most often expect to date, would try to date, and would like a partner of approximately his own social desirability. In brief, we attempted to apply level of aspiration theory to choice of social goals. A field study was conducted in which individuals were randomly paired with one another at a "Computer Dance." Level of aspiration hypotheses were not confirmed. Regardless of S's own attractiveness, by far the largest determinant of how much his partner was liked, how much he wanted to date the partner again, and how often he actually asked the partner out was simply how attractive the partner was. Personality measures such as the MMPI, the Minnesota Counseling Inventory, and Berger's Scale of Self- Acceptance and intellectual measures such as the Minnesota Scholastic Aptitude Test, and high school percentile rank did not predict couple compatibility. The only important determinant of S's liking for his date was the date's physical attractiveness.